The diabetes-related attitudes of health care professionals and persons with diabetes in Argentina - Gagliardino, Juan José (2007)
Objective. To test diabetes-related attitudes of health care team members (HCTMs) and people with diabetes in a developing country, in this case, Argentina. Methods. The third version of the Diabetes Attitudes Scale (DAS-3) was randomly administered, in person, to 252 HCTMs (nurses, nutritionists, physicians, podiatrists, and social workers) and 279 people with type 1 or type 2 diabetes mellitus in several provinces of Argentina in 2004. Data from 531 completed questionnaires were included in the study. The data were statistically analyzed using analysis of variance, covariance, chi-square, and t-tests. Results. Although few, the differences in attitudes of HCTMs and people with diabetes were significant. The two groups expressed only slight agreement on DAS-3 statements such as “seriousness of type 2 diabetes,” “value of tight control,” and “psychosocial impact of diabetes;” and disagreed completely on “patient autonomy.” No significant differences were recorded between people with type 1 or type 2 diabetes regarding “seriousness of the disease,” but from both groups, those individuals who had previously attended a diabetes education course assigned this statement a higher score (P < 0.01). Conclusions. The unfavorable trend among the participants, similar to that recorded in developed countries, would contribute to the poor treatment outcomes observed in people with type 2 diabetes. Changing these attitudes by means of education could contribute to improving the quality of care and of life for people with diabetes and to decreasing the cost of the disease.